“Now we start to make it like home”: reunited refugee families negotiating integration and belonging - Kerlaff, Leyla (Frontiers in Political Science, 2023)
This paper highlights the importance of local and individual context in either facilitating or hindering processes of integration for reunited refugee families settling in unchosen areas. It adds to understandings of integration by analysing the day-to-day active and processual nature of place-making, from the perspective of families. The findings are based on qualitative interviews with 13 refugee families -21 parents and 8 children aged between 12-18, who had recently been reunited in two large cities in the UK: Glasgow and Birmingham. The paper explores the local conditions families identified as conducive to settling in their local area and argues that the process of attaching to their new locales was mediated through the social connections they made. The article contributes to knowledge by demonstrating how families exercised agency and resilience in place-making in unchosen spaces, through the people they met and the relationships they developed. Further, it critiques the tendency to denigrate 'exclusive' bonding ties, particularly between co-ethnics and pays attention to the role of friendship in routes to belonging in unchosen spaces.